Analysis of the tourism potential of a territory: Application of the READI methodology in a natural reserve of Tandil, Buenos Aires, Argentina (Biocenosis, 2024)
The Sierra del Tigre Natural Reserve (RNST), located in Tandil, Buenos Aires Province, Argentina, represents a unique enclave of biodiversity, geodiversity, and cultural heritage in a peri-urban context. This study aims to evaluate the tourism development of the RNST using the READI matrix methodology (Resources, Actors, and Dynamics), specifically adapted for the analysis of the reserve and its surroundings. Through a mixed-methods approach, which includes the qualitative and quantitative analysis of the available resources, the participation of the subjects involved and the territorial dynamics, the strengths and weaknesses of the RNST were identified. The results highlight the valuable natural and cultural heritage of the area, while underscoring the need to diversify the funding sources, improve the tourist infrastructure and strengthen the community participation and territorial leadership. These actions are crucial to ensure a balanced and sustainable tourism development.
Keywords: Tandil; biodiversity; geodiversity; tourism development; READI matrix